Influence of Si-nanocrystal distribution in the oxide on the charging behavior of MOS structures - Tseng, Ampere A. (2010)
In this brief, the electrical characteristics of MOS structures with specially designed distributions of Si nanocrystals (nc-Si) embedded in the oxides were investigated, and very different behaviors in the electrical characteristics are observed as a result of the difference in the nc-Si distribution. For the case of nc-Si being confined in a layer in the oxide close to the gate, charging and discharging the nc-Si lead to a shift in the flat-band voltage, and a small difference in the location of the peak concentration of nc-Si can yield a large difference in the memory programming characteristics. However, for the case of nc-Si distributed throughout the oxide with a high concentration, charging and discharging the nc-Si cause a modulation in the capacitance magnitude instead of the flat-band voltage shift. The difference between the two cases highlights the importance of the nc-Si distribution in the memory device applications of the nc-Si.